1986
DOI: 10.1084/jem.164.6.2006
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid A gene family expression in different mouse tissues.

Abstract: Serum amyloid A (SAA) is a major acute-phase reactant and apoprotein of high density lipoprotein (HDL). SAA is encoded by a family of three active genes. We examined hepatic expression and searched for extrahepatic expression of the three SAA mRNAs after injection with casein or LPS. Studies using an SAA cDNA, which detects all three SAA mRNAs, revealed that after casein injection liver SAA mRNA was elevated approximately 1,000-fold. Adrenal gland expressed SAA mRNA at a low level (0.5% of hepatic level), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 41 publications
7
121
0
1
Order By: Relevance
“…Three SAA isoforms have been reported in mice. Saa1 and Saa2 isoforms are mainly expressed by hepatocytes, whereas the Saa3 isoform has been found to be induced in various tissues during inflammation (5,6). Under acute inflammatory conditions, such as infection, tissue damage, inflammation, and cancer, Saa1 and Saa2 are similarly induced, and serum SAA levels increase as much as 1000-fold (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Three SAA isoforms have been reported in mice. Saa1 and Saa2 isoforms are mainly expressed by hepatocytes, whereas the Saa3 isoform has been found to be induced in various tissues during inflammation (5,6). Under acute inflammatory conditions, such as infection, tissue damage, inflammation, and cancer, Saa1 and Saa2 are similarly induced, and serum SAA levels increase as much as 1000-fold (6).…”
mentioning
confidence: 99%
“…Saa1 and Saa2 isoforms are mainly expressed by hepatocytes, whereas the Saa3 isoform has been found to be induced in various tissues during inflammation (5,6). Under acute inflammatory conditions, such as infection, tissue damage, inflammation, and cancer, Saa1 and Saa2 are similarly induced, and serum SAA levels increase as much as 1000-fold (6). Induction of the genes encoding SAA1 and SAA2 during inflammation is triggered by elevated secretion of proinflammatory cytokines, such as IL-6 and TNF-␣, into the circulation and in hepatic cells (7,8).…”
mentioning
confidence: 99%
“…In response to a proinflammatory stimulus, the liver produces the isoforms 1.1 and 2.1, while SAA3 is mainly expressed in extrahepatic tissues [8][9][10]. More specifically, SAA3 does not contribute to circulating levels of SAA and has been related mostly to the promotion of local inflammation [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…11 SAA1 and SAA2 expression is restricted to the liver, intestine and kidneys whereas SAA3 is more widely expressed in mouse tissues. 13,16 In contrast, SAA1 is expressed in human adipocytes and its expression is increased in hypertrophic adipocytes from obese individuals. 17 Thus we speculated that mouse SAA3, which is upregulated in the adipose tissue of obese mice, 18 might be functionally similar to human SAA1 and perhaps represent a link between low-grade inflammation and metabolic diseases associated with obesity such as insulin resistance.…”
Section: Saa3 As a Mediator Of Metabolic Inflammation In Adipose Tissmentioning
confidence: 99%
“…Stimulating cultured colonocytes with LPS revealed that microbial components qRT-PCR screen of adipose tissue. 11 Since intraperitoneal injections of purified lipopolysaccharide (LPS) increases adipose expression of SAA3, 13 we hypothesized that the gut microbiota may induce signaling through Toll-like receptors (Tlrs), which recognizes conserved microbial structures such as LPS.…”
Section: Microbial Regulation Of Saa3 Expression In the Colonmentioning
confidence: 99%